Synergisticity Of District National Zakat Amil Agency, Zakat Amil Institution And Pati Regional Government In Zakat Management - Mu’arif, Samsul; Akhyak, Akhyak; Nurrahman, Dede (Publisher Cv. Inara, 2024)
This research is motivated by the phenomenon of the existence of two groups managing zakat (government and society) making up two large parts of the field of zakat management in Indonesia. The government and its institutions are used as the main focus of zakat collection targets by the National Zakat Amil Agency (BAZNAS) while the general public and private companies are more targeted objects for zakat collectors by the National Zakat Amil Institute (LAZNAS). In terms of legal regulations, the implementation of zakat in Indonesia shows cooperation between BAZNAS and the government to collect zakat funds from government employees to all institutions. However, in reality the results of collecting zakat, infaq and alms are still far below the existing potential, so there is still a need for synergy in various fields for the two groups of zakat managers. The aim of this research is to find out how there is communication synergy, coordination synergy and innovation synergy between the Pati National Amil Zakat Agency, the Amil Zakat Institute and the Regional Government of Pati Regency in managing zakat. This type of research uses qualitative research methods with the researcher as the key instrument in recording and collecting data through interviews, observing, collecting documents from zakat collection institutions and the Pati district government. Meanwhile, data analysis was carried out using an interactive analysis model. The results of this research conclude that 1. The form of communication synergy between the National Amil Zakat Agency of Pati, the Amil Zakat Institute of the Ministry of Religion of Pati and the Regional Government of Pati Regency is carried out formally by invitation or coming directly to the institution, or communicating using a digital platform by prioritizing the context of mutual brotherhood. need in managing zakat. The messages conveyed in the communication process are of high quality because the language is communicative, the message content is needs-oriented and delivered in a friendly manner. Feedback from communication shows support, openness and sincerity as well as high enthusiasm and commitment. 2). The form of coordination synergy is coordination synergy in planning, potential, cooperation in zakat education, distribution, joint program synergy and synergy in reporting. The mechanisms for coordination synergy include goal setting, stakeholder identification, payroll collection. Coordination synergy in monitoring and evaluation by sharia auditors or public accountants. 3). Synergy of innovation is carried out in Strengthening Zakat Regulations including the issuance of Regent's regulations on zakat, the issuance of regional regulations on zakat, b. Institutional strengthening includes the development of new UPZs, collaborative data analysis with religious instructors, routine quarterly coordination with fellow zakat managers, c. Program synergy, including zakat education with socialization and guidance of UPZ, distribution of zakat other than ashnaf 8, distribution of zakat for disaster response